A Study of Prosocial Trends of Mothers with Children with Down Syndrome - Mambetalina Gaukhar; Aubakirova Zhanat; Medetbekova Anar; Burganova Roza (SHS Web of Conferences, 2025)
This article explores the prosocial inclinations of mothers with children who have Down syndrome, aiming to identify the traits that shape their prosocial behaviors. Given the limited research on the unique personal characteristics of these mothers, the study seeks to fill this gap by investigating the various components of prosocial behavior in this specific population. The research analyzes prosociality across six distinct behavioral categories: compliant, published, anonymous, emergency-directed, emotional expressive, and altruistic behaviors. A rigorous empirical methodology was employed, including the adaptation of the G. Carlo and B.A. Randall prosocial tendencies framework, with statistical analysis to uncover the psychological and socio-psychological factors influencing these behaviors. The results highlight a complex structure of prosociality, emphasizing individual differences in how these mothers respond to various social contexts. The findings suggest that these mothers exhibit a unique blend of social responsiveness, shaped by both personal and situational factors. The study contributes valuable insights into the psychological profile of mothers caring for children with Down syndrome, shedding light on their internal motivations and the broader implications for social support and intervention programs. The implications of the study underscore the importance of understanding these mothers’ prosocial behaviors for targeted interventions and support mechanisms.